A novel design using a virtual control group to evaluate non-inferiority of nevirapine and lamivudine dual maintenance in HIV therapy - Alessandro Suter; Markus Bickel; Carsten Depmeier; Peter Gute; Gaby Knecht; Marcel Stöckle; Christoph Fux; Baharak Babouee Flury; Patrick Schmid; Pietro Vernazza; Christian R. Kahlert (PLoS ONE, 2026)
Purpose Reducing the number of drugs in combined antiretroviral therapy (cART) likely reduces toxicity. We hypothesized that dual therapy (DT) with nevirapine (NVP) and lamivudine (3TC) would be non-inferior to a virtual control without treatment failure. Methods This multicenter study enrolled patients on cART with HIV plasma viral load (pVL) <50 cp/ml for ≥2 years and on NVP for ≥6 months. Patients were compared to a simulated virtual control group with an assumed failure rate of zero. Those with prior Non-Nucleoside Reverse Transcriptase Inhibitor failure or 3TC resistance were excluded. Treatment was simplified to DT with NVP/3TC for 48 weeks, with quarterly pVL-measurements. The primary endpoint was confirmed virologic failure (pVL ≥ 200 cp/mL). A 4% non-inferiority margin and sample size of 201 were set, with a stopping rule if three virologic failures occurred. Results From April 2019 to January 2023, 201 patients from five centers in Switzerland and Germany started DT, which 194 participants completed. Two patients (1.03%, 95% CI: –0.92% to 3.68%) reached the primary endpoint for failure due to adherence issues. No additional failures were observed during a 12-month post-study follow-up of 184 participants. Conclusions Simplification to NVP and 3TC was as effective as the ideal virtual control. However, the results of NVP and 3TC maintenance therapy are only applicable to people living with HIV who meet the study’s inclusion and exclusion criteria. Virtual controls could improve research efficiency and warrant further evaluation.